El juicio en el proceso penal Colombiano comparado con los estados unidos de america (2015)
The human race by nature tends to lives ¡n community where grows and develop new abilities that improve the evolution of the thoughts, team work and daily life. All those situations make necessary that the people counts with several norms and principies of justice that conforms the normative order of a society. In this article that normative order will know as criminal law whose objective is the search of the truth with the purpose of keep the respect, and protect íhe peace in the case that may have an aggression to the legal interests under the law in a particular or collective way. Nowadays each country according to their culture has his own rules in the criminal process to judge and condemn the people that unrespect the norm. For the development of this article the main topic is the trial, A!so the steps of the trial will be explained and the judicial structure in two different examples: one in the United States and the other in Colombia. In both cases, the roles of the iawyers, prosecutors, judges, the jury have and important task to determínate the guiltiness or innocents of the accused